Still searching for the wage curve: evidence from Germany and Italy - Andreas Ammermüller; Claudio Lucifora; Federica Origo; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
This paper investigates the functioning of regional labour markets in Italy and Germany for different employee groups. In the light of high and persistent differences in unemployment and wage rates between the North and South of Italy and the West and East of Germany, we first derive theoretical hypotheses on group specific correlations between regional unemployment and individual wages. Using micro data on hourly wages properly matched to local unemployment rates, we specify and empirically test different wage equations. On the basis of our results, we find no evidence for the existence of a ?wage curve? in Italy. In the case of Germany, results are quite sensitive to the model specification and the employee group considered. In both countries, the reaction of wages to local unemployment varies significantly along the wage distribution, being more sensitive around the median quantiles. We conclude that there is no uniform wage curve and call for a differentiated analysis for various groups, taking into account the respective institutional setting.
Keywords: J6; J3; R1; 330; wage curve; local labour markets; quantile regressions